Continuous quality improvement in module development in an ODL institution - Chiam , Chooi Chea; Woo, Tai-Kwan; Lim , Szu Ming (2019)
Open University Malaysia (OUM) is an open distance learning (ODL) institution; adopting the blended learning pedagogy which provides flexibility and timeeffectiveness for self-paced study to its learners. Learners do self-learning most of the time. This calls for quality learning materials to support the learning process in an ODL setting. OUM responded to this call by leveraging on Internet-based technology to deliver educational content such as e-modules, video lectures, e-forums etc. to its learners. Learners can now access the University’s e-content (2,431 e-modules and 288 video lectures) anytime, anywhere, via OUM’s learning management system, myINSPIRE. Using descriptive and inferential statistics as the main analytical tool, this study aims to gain insight into learners’ feedback on one of the core learning materials – the e-modules. Responses from learners from various programmes and clusters were collected via online surveys for two semesters (January 2018 and May 2018). A total of 238 and 488 learners responded to the January and May surveys respectively. This paper discusses thee-modules in 10 dimensions from the instructional design perspective encompassing areas such as the design, formatting, self-check and activity questions, organisation of the content, ease of reading, graphics as well as overall satisfaction. The results of this study would be able to provide some insights to the education provider on the quality of the e-modules from the instructional design perspective. (Abstract by authors)